Integration of EDS Values Through The PBLHS Movement for Strengthening Environmental Care Character in Islamic Primary School - Ardila, Diajeng Septia Winni; Hanik, Elya Umi (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2026)
This study analyzes the integration of Education for Sustainable Development (ESD) values through the Environmental Care and Culture Movement in Schools (PBLHS) to strengthen environmental care character at MIN 4 Demak. The issue is important because schools should not merely promote cleanliness habits, but should connect environmental awareness with ecological sustainability, social responsibility, and prudent resource use. The research employed a qualitative case study approach. Data were collected through interviews, observation, documentation, and analysis of the school profile, the four-year PBLHS plan, monitoring and evaluation reports, and interview guidelines. The findings show that ESD values were integrated through written planning, daily habituation, environmental learning integration, teacher role modelling, and periodic evaluation based on behavioral change and physical environmental conditions. Core activities included waste sorting, 3R practices, water and energy conservation, greening programs, seedling cultivation, tree planting, biopore development, and campaigns to reduce plastic waste. The study indicates that PBLHS not only cultivates cleanliness habits but also develops responsibility, discipline, cooperation, and sustainability awareness among students. Therefore, integrating ESD values through PBLHS has proven effective in strengthening environmental care character contextually and sustainably